Is It Time to Review our Educational Program for the Electrocardiography Operators? - Saadat, Habibollah; Tajdini, Hossein; Saadat, Zahra; Eslami, Vahid; Sheibani, Mehdi; Sharifkashani, Babak; Sadeghi, Roxana; Khaheshi, Isa (International Journal of Cardiovascular Practice, 2017)
No abstract available.